Improving passenger satisfaction at Kuwait International Airport by using multi-objective optimisation - Alsaber, Ahmad (2024)
Efforts to optimise the quality of services that passengers experience during the check-in process at major airport terminals are important discriminators in deciding the overall quality of the airports themselves. Improvement of passenger services during check-in involves reduction in queues and waiting times. This however, may require additional expansion projects to be undertaken by the authority. Nevertheless, such expansion projects involve conflicting ideas from multiple interest groups due to the absence of any existing efficient simulation model. This paper presents a multi-dimensional approach towards finding an optimal and feasible solution to the resource allocation problem at check-in stages in airports. The proposed methods employ optimisation techniques such as mixed integer goal programming (MIGP) and genetic algorithm (GA) to offer a comparative multi-solution outcome towards optimising the passenger quality of services at airport departure check-in. By adopting the proposed approaches, one can expect to achieve the following objectives: 1) finding an optimum allocation for airlines to different check-in zone area; 2) obtain a feasible planning to undertake decisions concerning check-in area expansion projects reaching their desired goals to improve passenger level of service under limited budget and area space.